«GREEN FLOORS" – THE FUTURE OF ECOLOGICAL CITIES - VASYLYNYCH, ANASTASIІA; KYRYTSYA, INNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
In this work the project of a multi-story ecological residential building with «green floors» is developed and original ideas are proposed that will reduce the negative impact of construction on the environment and improve people's quality of life. «Green floors» are floors, the area of ​​which is decorated with flower beds and vertical gardens, as well as recreation areas. «Green floors» play the role of an oxygen station (having a positive effect on the environment), inter-floor sound insulation, reduce wind load and increase fire safety, allow developers to build more densely by reducing the area of ​​adjacent park areas. The increase in environmental trends in construction is due to several factors. One of the most important factors is the growing awareness of people about the impact of construction on the environment and human health. The threat of climate change and environmental crises has caused increased interest in ecological construction. In the proposed project, the roof of the house can be profitably used, receiving electricity not only with the help of solar panels, but also wind generators and hydro generators. By combining these three alternative energy systems, maximum energy accumulation can be achieved. «Green floors» are the future of high-tech ecological cities, which will not only add aesthetic charm to the urban landscape, but also bring tangible benefits. The construction of ecological residential buildings will solve environmental problems, improve the psycho-emotional state of people, and also save on electronic media. Today's «green houses» are built quickly with relatively low cost, combining cost-effective solutions for energy carriers, and therefore have great potential for developers. The results obtained in the work can be used by specialists in the field of construction.
Keywords: «green floors»; ecological houses; ecological cities